Fallimento (Altre Modernità, 2017)
The play focuses on the final debate in a presidential campaign. The two candidates are Richard III, unapologetic and ruthless, and Lady Macbeth, whose goal is power. Between them as a moderator there's Falstaff, who is forced to relinquish his comic personality.